PERILAKU MAHASISWA PENGHOBI DOMINO DI KAWASAN KAMPUS PERGURUAN TINGGI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN - Rahmi, Miftahur; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Behavior is all the directly activities or indirectly observable by outsiders. Deviant behavior is an action that does not conform in the values and social norms. At present, many students were playing dominoes at the small stalls around the college. The symptoms of playing dominoes make many students do the deviation when playing by risking something, one of them bet the food and drinks. The aim of this research is to determine the behavior and the impact on students' academic achievement domino hobbyist. The theory used in this research is the theory of deviations, Theory of Behavior distorted (Deviant Behavior) by Paul B. Harton (Elly M.Setiadi, 2011). This research used a qualitative method. The data analysis done by qualitative description, the technique of collection data in this study is accidental where the respondents amount 4 students. To collect data in this researcher used the method of observation, documentation and interview using interview guide. From this research it can be concluded that students become anger and have a bad speak when they get bad stone. The hobby playing domino has bad affect to the student’s achievement and inclined get low cumulative index achievement and the average of index achievement is down.Keywords: Behavior, students, the gamer of dominoes.